2017
DOI: 10.1093/schbul/sbx028
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Commonalities and Distinctions Among Three Major Psychiatric Diagnostic Categories: A Structural MRI Study

Abstract: Our findings of common alterations in SZ, BD, and MDD support the presence of core neurobiological disruptions in these disorders and suggest that neural structural distinctions between these disorders may be less prominent than initially postulated, particularly between SZ and BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
47
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 45 publications
8
47
2
Order By: Relevance
“…[9][10][11] Abnormal oligodendrocyte function and demyelination have been associated with alterations in white matter integrity in the 3 disorders. 7,12,13 Moreover, MRI studies have found commonalities in alterations in white matter integrity among schizophrenia, bipolar disorder and MDD, [14][15][16][17][18][19] with more prominent alterations in schizophrenia and bipolar disorder than in MDD. 20 Increasing attention has been focused on white matter net work alterations in schizophrenia, bipolar disorder and MDD.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Abnormal oligodendrocyte function and demyelination have been associated with alterations in white matter integrity in the 3 disorders. 7,12,13 Moreover, MRI studies have found commonalities in alterations in white matter integrity among schizophrenia, bipolar disorder and MDD, [14][15][16][17][18][19] with more prominent alterations in schizophrenia and bipolar disorder than in MDD. 20 Increasing attention has been focused on white matter net work alterations in schizophrenia, bipolar disorder and MDD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroanatomical pattern recognition studies attempted to distinguish individuals with schizophrenia by structural magnetic resonance imaging (sMRI) and diffusion tensor imaging (DTI). 1,2 Applications of cutting-edge machine learning approaches in structural neuroimaging studies have revealed potential pathways to classification of schizophrenia based on regional gray matter volume (GMV) or density or cortical thickness. [3][4][5] Additionally, cortical folding may have high discriminatory value in correctly identifying symptom severity in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have addressed similar questions , our work is the first to use multivariate methods to assess the relationship between volumetric patterns and symptom severity and is also the first to investigate this relationship across unipolar and bipolar depression.…”
Section: Introductionmentioning
confidence: 99%